Nitrogen cycling genes abundance in soil and aboveground compartments of tropical peatland cloud forests and a wetland on Réunion Island - Fahad Ali Kazmi; Ülo Mander; Reti Ranniku; Maarja Öpik; Kersti Püssa; Kaido Soosaar; Kuno Kasak; Mohit Masta; Claudine Ah-Peng; Mikk Espenberg (Scientific Reports)
Abstract Peatland cloud forests, characterized by high altitude and humidity, are among the least-studied tropical ecosystems despite their significance for endemism and the bioavailable nitrogen (N) that can be emitted as N2O. While research has mainly focused on soil, the above-ground microbial N cycle remains largely unexplored. We quantified microbial N cycling genes across ecosystem compartments (soil, canopy soil, tree stems, and leaves) in relation to N2O and N2 fluxes and soil physicochemical properties in two peatland cloud forests and a wetland on Réunion Island. Complete denitrification minimized N2O emissions and increased N2 fluxes in wetland soils. In cloud forest soils, archaeal nitrification primarily produced nitrate (NO3 –), while low pH potentially slowed denitrification, resulting in minimal N2O emissions. Soil N-fixers were more abundant in Erica reunionensis-dominated forests than in mixed forests. Tree stems varied between weak N2O sinks and sources, with fluxes unrelated to gene abundances in stems. High prokaryotic and fungal nirK gene abundance in forest canopy soil suggests potential for above-ground denitrification in wet conditions. nosZ-I genes found in forest canopy soil and leaves (E. reunionensis, Alsophila glaucifolia, and Typha domingensis) indicate that plants, including forest canopy, may play a significant role in the reduction of N2O.